Peranan JICA dalam Konservasi Mangrove di Indonesia Sebagai Bagian dari Program The Project For Mangrove Ecosystem Conservation And Sustainable Use in the ASEAN Region (MECS) - Parama Putra, Pande Gede Aditya; Priadarsini, Ni Wayan Rainy; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2017), 2017)
ABSTRACT The study was based on concerns of Japan through JICA (Japan International Cooperation Agency) in the conservation of the site as we know Indonesia is one country in ASIA which has Mangrove forest widest, because of a lack of awareness of the public on the importance of mangrove forests and their functions mangrove forests eventually many mangrove forests are dying and unkempt . After comprehensive research, it can be seen in the role of JICA Program The project For Mangrove Ecosystem Conservation And Sustainable Use in the ASEAN Region (MECS). In this advanced program JICA has a role as a conduit means and held a workshop on how your way of preserving and caring for the mangrove forests are good in order not to die. Here, JICA also inviting countries - other countries to participate in this program for sharing mangrove problems in their country and how they handle it.   Keywords: JICA, MECS program, Pelestraian mangrove forests, Share and Learning